أثر عرض النقود على التضخم في الاقتصاد الليبي خلال الفترة من 1990-2020 (Comprehensive Journal of Science, 2025)
The study aimed to examine the varying role played by the money supply in influencing inflation in Libya. It explored the concept of money supply in both its broad and narrow definitions and presented data covering the period from 1990 to 2020.The findings from the data revealed that the money supply had a significant impact on inflation during certain phases of the study, while in other phases, its effect was minimal. This variation was attributed to multiple factors influencing inflation beyond the money supply itself. The country experienced several periods of internal and external pressures, such as the international sanctions, the 2011 war, and the subsequent crises. The researcher recommended promoting electronic payment systems and encouraging citizens to shift toward digital transactions instead of cash payments. Additionally, economists and policymakers should strengthen monetary policy to achieve greater economic stability.